The Folktale: Its Origin and Sociological Function - Rehim, Mastur (Al-Mukhtar Journal of Social Sciences, 2026)
Based on its constituent characteristics, researchers figure out that the folk tales focus on one dimension in their stories and neglect the rest of the dimensions. Usually, the story in a folk tale is superficial and involves integrated events based on depictive narratives but it is usually disconnected from reality. There is no doubt that folk tales, myths and fables have origins otherwise they would not have survived in people’s minds and would not have been passed on from one generation to another. Therefore, the objective of this study is to identify the nature, function and root of the folk tale as being metaphysical, religious, anthropological, ideological, intellectual, or perhaps just a product of social imagination to explain some of the experienced events. In this study, the analytical approach is adopted to analyze the content of sample folk tales in their social contexts. The study findings indicate that people’s resort to folk tales is a kind of escape from their failures and a compensation for their inability to confront or explain them. Thus, folk tales and highly respected tradition have formed the logic of people’s extreme imagination of all aspects of their struggle in life. This imagination has provided a way out for people from the tensions of their history through the imaginary employment of fables and folk tales about heroes and legends to compensate for what they could not achieve in their reality. Perhaps the problem that Arab societies suffer from is the unobjective adherence to and regret of the past and its values, which made these societies search for what they miss through miracles or paranormalities that may rescue them from their miserable conditions.